Hubungan antara narsisme dengan presentasi diri pada pengguna jejaring sosial facebook - Pangastuti, Herlina; , Dr. Taufik, M.Si (2015)
The presentation of self is an effort consciously or unconsciously to influence someone with the impression created by the appearance of or behavior. With the development of technology and information growing, Facebook became one of the social media interest by wide audience. In 2010 Facebook users in Indonesia is about 24 million or 10 percent of the total population of Indonesia. Facebook has become a new way for activities of self-presentation. Factors affecting the presentation of self, including Narcissism. The purpose of this study is to determine the relationship between Narcissism with self-presentation, as well as determine the level of self-presentation and narcissism facebook users. With the hypothesis of a positive relationship between narcissism with self-presentation. The subjects were students of psychology faculty at one PTS in Surakarta numbered 67 people. Sampling technique in this research is purposive sampling. Measuring instruments used is narcissism scale and the scale of self-presentation. The data analysis method product moment correlation technique.Based on the results of data analysis known that there is a positive relationship significantly between narcissism with self-presentation on social networking users facebook, indicated by the value (r) of 0.287; (P) = 0.019 (p> 0.05),based on the value that is obtained in the self-presentation of empirical mean (RE) of 62.30 and the mean hypothetical (RH) of 55 which means that the level of self-presentation the subject is high. Variable narcissism has the empirical mean (RE) amounting to 63.55 and the mean hypothetical (RH) of 70 which means narcissism in the subject was moderate.